Lateral Translation of the Patella in MPFC Reconstruction: A Biomechanical Study of Three Surgical Techniques (210). Issue 10 (31st October 2021) - Cregar, William; Huddleston, Hailey; Shewman, Elizabeth; Cole, Brian; Yanke, Adam
Objectives: Recurrent patellar instability (RPI) is a common knee disorder and can lead to chronic pain and functional disability. Surgically addressing recurrent patella instability has classically focused on reconstruction of the MPFL, which has widely become the standard of care either in isolation or concomitantly with other patellar realignment procedures. Complications following MPFL reconstruction include patellar fracture, articular surface penetration, and physeal injury in skeletally immature patients. In an effort to avoid these, other surgical techniques have been described. While these alternative MPFC reconstructions have anatomical support and the theoretical potential to reduce complications, it is unknown whether differences exist in lateral patellar translation and thus their effectiveness in adequately stabilizing the patella. The purpose of this study was to investigate whether differences exist in the ability to prevent lateral patellar translation between three distinct medial patellar stabilizing surgical procedures at varying knee flexion angles. Methods: Six cadaveric knee specimens were dissected, potted, and placed in a customized jig for testing. The quadricep muscle groups were separated into three components and loaded with a total of 175 N in anatomic directions using a weighted pulley system. Lateral patellar displacement was measured at 0°, 10°, 20°, 30°, 45°, 60°, and 90° of knee flexion using a tensile testing machine with a 20 N lateral force applied to the patella. Each specimen was tested with the MPFC intact and sectioned, and after each of the three reconstruction techniques: medial patellofemoral ligament (MPFL) reconstruction, hybrid (proximal medial patellar restraints - PMPR) reconstruction, and medial quadriceps-tendon femoral (MQTFL) reconstruction. Statistical analysis used the Friedman and Wilcoxon rank sum tests due to non-normally distributed data. Results: There was significantly increased lateral patellar displacement following MPFC sectioning when compared to the intact state in early degrees of flexion (10° to 30°) (p<0.05). All three reconstruction groups adequately restored patella stability and reduced lateral patellar displacement following medial soft tissue sectioning by 42%, 41% and 33% following MPFL, Hybrid and MQTFL reconstruction, respectively, from 0° to 30° of knee flexion (p<0.05 for each reconstruction group). When compared to the native, intact medial restraints group, all three reconstruction groups demonstrated reduced patella translation at full knee extension, while the MPFL and Hybrid reconstruction groups additionally demonstrated significant reduction of patella translation at 10° of flexion as well (p<0.05). When comparing patella displacement between reconstruction groups, no significant difference was observed at any degrees of flexion between the three groups. Conclusions: This biomechanical cadaveric study demonstrates the efficacy of three different MPFC reconstruction techniques in restoring patella stability following MPFC sectioning, especially at lower knee flexion angles where the medial soft tissue restraints play a more important role. Although all three reconstruction groups demonstrated less patella translation than the native MPFL intact knee, MPFL reconstruction appears to provide the most robust patella stabilization, whereas MQTFL reconstruction may be the most forgiving construct. Future clinical studies are needed to investigate the clinical correlation of these findings.